Pengaruh Pemberian Asap Cair Melalui Air Minum Terhadap Kualitas Karkas Ayam Broiler - Meisji Liana Sari; Fitri Nove Liya Lubis; Lia Dwi Jaya (Agricultural Faculty, 2014)
(The Effect of Wood Vinegar Through to The Drinking Water on The Quality of Broiler Chicken Carcass)ABSTRACT. This aims of this research was to determine the percentage of carcass, commercial carcass parting and meat bone ratio (breast, thigh and wing) of broiler consumed wood vinegar. This research was assigned into used Completely Randomized Design (CRD) with 5 different treatments and each 3 replicates. The treatments were dose of wood vinegar, R0 = water + 0% wood vinegar, R1 = water + 0.25% wood vinegar, R2 = water + 0.5% wood vinegar, R3 = water + 0.75% wood vinegar, R0 = water + 1% wood vinegar. The observed parameters were percentage of carcass, commercial sliced carcass parting and meat bone ratio. The results showed that wood vinegar in the drinking water did gave not significantly (P0,05) effect to the percentage of carcass, commercial sliced carcass parting and meat bone ratio of broiler chickens. It is concluded that Liquid wood vinegar can be used for broiler chickens until 1%.